Her forbidden firefighter - Douglass, Traci (Douglass, Traci. Wyckford General Hospital, 2024)
Physical therapist Luna was aware of aloof firefighter Mark as soon as he arrived in town. But she's been hurt before, so relationships are forbidden. Then on a hike gone wrong, Luna needs rescuing, and in Mark's protective orbit, she gets a taste of how steamy things could be between them. And as the heat turns up, it gets harder to deny herself what she truly wants...